Fostering students' mathematical modeling skills through a hadith-based contextual learning - Nasution, Eline Yanty Putri; Anggraini, Reri Seprina (Al-Jabar: Jurnal Pendidikan Matematika, 2026)
Purpose: This study aims to describe students’ mathematical modeling skills by contextualizing situations derived from their familiar religious knowledge. The learning process is implemented through Hadith-Based Mathematics Learning in the Integration of Mathematics and Islamic Values course. Method: A Descriptive Quantitative approach was employed to profile students’ post-instruction mathematical modeling performance in a single cohort to analyze how students construct mathematical models based on four Hadiths about the Virtues of Prayer. The research subjects were 12 fifth-semester students from the Mathematics Education Department in the 2025/2026 academic year who enrolled in the course. Data were collected through mathematical modeling tests. The research process consisted of preparation, data collection, and analysis, followed by the interpretation and discussion of the findings. At the final stage, students’ levels of mathematical modeling ability were categorized from level 0 to level 5. Findings: The results revealed that students developed several mathematical models based on the Hadiths of the Virtues of Prayer, including ratio, algebra, functional, and arithmetic. Overall, students’ mathematical modeling ability fell within the good category, with an average achievement of 79%. While the average performance corresponded to level 4, level 5 was the most frequently attained level.Indicating well-developed modeling skills in solving and interpreting mathematical models. Significance: This study presents a contextual teaching approach, Hadith-Based Mathematics Learning, that provides a systematic pathway for integrating Islamic values into mathematics instruction. Therefore, this study serves as a reference for lecturers and curriculum developers seeking to harmonize scientific knowledge and Islamic values in mathematics education.